Franklin Endicott and the Third Key - DiCamillo, Kate; Van Dusen, Chris (Somerville, Massachusetts : Candlewick Press, 2021)
A constant worrier, Franklin Endicott earns a fresh cause for alarm when he accompanies Eugenia Lincoln to her favorite thrift shop and leaves with a mystery to solve.
Keywords: Thrift shops -- Fiction; Fear -- Fiction; Pigs -- Fiction